Checkpoint Inhibitors and Therapeutic Vaccines for the Treatment of Chronic HBV Infection - Hoogeveen, Ruben C.; Boonstra, André (Frontiers in Immunology, 2020)
Treatment of chronic hepatitis B virus (HBV) infection is highly effective in suppressing viral replication, but complete cure is rarely achieved. In recent years, substantial progress has been made in the development of immunotherapy to treat cancer. Applying these therapies to improve the management of chronic HBV infection is now being attempted, and has become an area of active research. Immunotherapy with vaccines and checkpoint inhibitors can boost T cell functions in vitro, and therefore may be used to reinvigorate the impaired HBV-specific T cell response. However, whether these approaches will suffice and restore antiviral T cell immunity to induce long-term HBV control remains an open question. Recent efforts have begun to describe the phenotype and function of HBV-specific T cells on the single epitope level. An improved understanding of differing T cell specificities and their contribution to HBV control will be instrumental for advancement of the field. In this review, we outline correlates of successful versus inadequate T cell responses to HBV, and discuss the rationale behind therapeutic vaccines and checkpoint inhibitors for the treatment of chronic HBV infection.